THE IMPLEMENTATION OF PEER CORRECTION TECHNIQUE TO TEACH WRITING REPORT TEXT TO THE ELEVENTH GRADERS OF SMAN 1 CERME (RETAIN, 2016)
THE IMPLEMENTATION OF PEER CORRECTION TECHNIQUE TO TEACH WRITING REPORT TEXT TO THE ELEVENTH GRADERS OF SMAN 1 CERME DESSY KARTIKA RIZKY English Education, Language and Art Faculty, State University of Surabaya dessyrizky@mhs.unesa.ac.id Dr. H. Aswandi, M.Pd English Education, Language and Art Faculty, State University of Surabaya aswandi@unesa.ac.id Abstrak Penelitian ini berkaitan dengan pengajaran menulis teks report dengan menggunakan tehnik peer correction. Peer correction adalah tehnik tehnik yang digunakan dalam pengajaran menulis dengan memasangkan siswa berdasarkan kemampuan menulis mereka. Penelitian ini mendeskripsikan pelaksanaan tehnik peer correction dalam pengajaran menulis teks report dan respon siswa terhadap pelaksanaan tehnik peer correction. Penelitian ini menggunakan deskripsi kualitatif sebagai metodologi penelitian. Peserta penelitian ini adalan seorang guru dan satu kelas sebelas SMAN 1 Cerme. Data penelitian diperoleh melalui lembar pengamatan, catatan, dan kuisioner. Hasil penelitian pertama berkaitan dengan pelaksanaan tehnik peer correction. Tehnik tersebut dapat diimplementasikan dalam pengajaran menulis. Guru dan siswa mampu mengaplikasikan semua tahapan dalam tehnik peer correction. Selain itu, proses belajar mengajar dapat berlangsung dengan baik. Hal ini dibuktikan dengan aktivitas guru dan siswa yang sesuai dengan tahapan pendekatan ilmiah dalam kurikulum 2013. Hasil dari kuisioner menunjukkan bahwa siswa menikmati proses belajar mengajar dengan tehnik peer correction karena tahapan-tahapannya dapat membatu mereka dalam mengungkapkan ide mereka menjadi tulisan yang teratur. Kata kunci : Tehnik peer correction, menulis, teks report. Abstract This study focuses on teaching writing report text by using peer correction technique. Peer correction is a technique in teaching writing through pairing the students based on the level of writing competence. Furthermore, this study describes the implementation of peer correction technique to teach writing report text and the students’ responses toward the implementation of peer correction technique. This study used descriptive qualitative as the research design. The participants of this study were a teacher and a class of eleventh graders of SMAN 1 Cerme. The data of this study were collected through observation checklist, field notes, and questionnaire. The first result was related to the implementation of peer correction technique. The technique could be implemented in teaching writing. The teacher and students could apply the steps of peer correction technique. In addition, the teaching and learning process could run well. It was proven by the teacher’s and students’ activities which were appropriate with the stages of scientific approach as 2013 curriculum suggested. The result of questionnaire showed that the students enjoyed teaching and learning process with peer correction technique since the procedures involved were helped them to express their ideas into well-organized writing. Keywords: Peer correction technique, writing, report text.